A novel learning environment for undergraduate mathematics courses - Andrade Aréchiga, María; G. Pulido, J. R.; Flores Cortés, Carlos A.; Reyes, Pedro Damián; Guerrero Ibáñez, Juan Antonio; Ramos Michel, Erika Margarita (Revista Colombiana de Computación, 2011)
This work presents a scaffolding design of learning objects as auxiliaries in the teaching-learning of mathematics at undergraduate level, through an electronic learning platform developed for using in formal mathematics courses. Its design is based on the results of surveying a group of mathematics teachers in the undergraduate fields of Science and Engineering in Mexico, about different aspects of their teaching practice. This survey is consistent with other national and international studies that highlight a series of problems found in the undergraduate fields of Science and Engineering. Guidelines for the development of this kind of learning objects were established, which leads to curricular changes that will result in an adequate process of integrating the use of technology in the classroom. An important feature of these objects is flexibility as they are helpful tools in the innovative design process. A grounded model for the creation of teaching materials is proposed, including elements that facilitate their use, and thus, it is concluded that the use of these tools is a factor that can help alleviate some of the learning problems currently present in undergraduate level mathematics courses.